(untitled) (Международный научный журнал «Инженер», 2026)
His scientific article provides a detailed description of the modern development trends of modified composite polymer materials used in mechanical engineering and other industries, their creation, tribotechnical properties, structural structure and practical application. The article presents the results of laboratory tests of polymer-based composite materials modified with organomineral fillers, their physicomechanical and tribological properties. The use of composite materials is of particular importance for parts of machines and mechanisms operating under high friction and load conditions. Such materials reduce the coefficient of friction on surfaces, are wear-resistant, reduce the generation of static electricity and extend their service life. In particular, their use in the fields of cotton processing, chemical industry, agricultural machinery and energy significantly increases efficiency. The article also analyzes the possibilities of improving the tribotechnical properties of composite polymer materials through their physicochemical and mechanochemical modification on a scientific basis. Based on various structural components and their ratios, optimal composite compositions were developed, and the most suitable options were identified based on the results of experiments conducted in laboratory conditions. The composite polymer materials developed in this scientific work are considered one of the promising areas for the mechanical engineering industry.